1993
DOI: 10.1111/j.1346-8138.1993.tb03826.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐microscopic Observation of a Human Epidermal Langerhans Cell in Mitosis

Abstract: Langerhans cells are dendritic cells of the epidermis originating from bone marrow precursors which may exceptionally undergo mitosis within the skin. We report herein an electron-microscopic observation of a dividing LC within a seemingly hyperproliferative human epidermis. This observation further underlines the self-reproducing capacity of LC in situ and suggests that LC may respond to the same mitogenic stimuli as keratinocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[35-38] Differentiated cells localize to the midepidermis, demonstrate characteristic Birbeck granules, and exhibit dendritic appendages. These differentiated cells, although usually stable, sometime exhibit proliferative activity and increase in many cutaneous immune response states [23,39,40]. The inability of PTU to reduce CD1a expression in biopsy samples of patients with psoriasis suggests that the mechanism of action of this drug is psoriasis is not due to any effect on skin antigen-presenting cells or production of IL-12, a motive cytokine that is responsible for initiation and maintenance of the cytokine stimulatory cascade that leads to formation of the psoriatic plaque [16].…”
Section: Discussionmentioning
confidence: 99%
“…[35-38] Differentiated cells localize to the midepidermis, demonstrate characteristic Birbeck granules, and exhibit dendritic appendages. These differentiated cells, although usually stable, sometime exhibit proliferative activity and increase in many cutaneous immune response states [23,39,40]. The inability of PTU to reduce CD1a expression in biopsy samples of patients with psoriasis suggests that the mechanism of action of this drug is psoriasis is not due to any effect on skin antigen-presenting cells or production of IL-12, a motive cytokine that is responsible for initiation and maintenance of the cytokine stimulatory cascade that leads to formation of the psoriatic plaque [16].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments based on in situ 3 H‐thymidine and BrdU incorporation showed that 2–3% of epidermal LC are cycling (5) and that murine epidermal LC express the Ki67 proliferation‐associated antigen (6). Several electron microscopic observations of LC undergoing mitosis within human epidermis have also been reported (7). Experimental data obtained in mice have suggested that under steady‐state conditions the efflux of LC to local lymph nodes would be balanced by LC divisions within the epidermis, whereas under conditions severely depleting epidermal LC (such as UV‐radiation), LC precursors would be recruited from the peripheral blood (8).…”
Section: Introductionmentioning
confidence: 93%
“…Although relatively stable in normal skin, Langerhans cells have been observed to show evidence of replicative activity 15–19 . Upon antigenic stimulation, Langerhans cells rapidly migrate from the epidermal layer into dermal lymphatics and ultimately to draining lymph nodes, where antigen presentation to large numbers of naive T cells can be most efficiently accomplished.…”
Section: Langerhans Cell: Life Historymentioning
confidence: 99%